Diseño de un sistema de filtrado para muestras de material arcilloso para un laboratorío de materiales - Marin S., Walter (2010)
The current thesis talks about of the design of an industrial ventilation system to categorize samples from dried milled clay for its sized analysis in the Laboratory of Ceramics, which consist in separating the particles by the grain size, obtaining an approximation of the percentage of materials that conforms the sample, especially the oxides, which was born from the necessity to improve the present system, in particular, the time it takes to develop the practice. The new system is based on methods for transportation of solids in controlled air waves and filtration of air – solid combination, which applies serial cylinder filters, arranged in the format to capture the largest particles ranging from 190, 140, 90, 40 and 5 μm. It must contain a cleaning system that runs on pulses of air for recollection of the different particles.